Identifying of Entrepreneurship Behaviors: Case of Country in Transition Economy - Khorakian, Alireza; Monfared, Mahmood; Shirazi, Ali; Maharati, Yaghob (International Journal of Supply Chain Management, 2019)
Successful companies recognize that the most important elements in the organization are the ability to use the creativity of managers and their employees through the recognition of their behaviors. One of the most important strategies for developing Entrepreneurship in organizations is to improve and enhance the Entrepreneurial behavior of employees and sustainable supply chain management, but what is to be deduced from the review of the history of the research is that most of the research in the field of Entrepreneurship personality has featured them. Less focused on behaviors, especially in developing countries and transition economies. The research is part of a series of research that seeks to identify and identify the components of Entrepreneurial behavior in the organization in Iran as a developing country, which is one of the economies in transition. This research is a qualitative research in which a thematic analysis approach has been used. The statistical community of this research is capable of employing 170 employers. The findings of the study showed that 27 components of Entrepreneurial behaviors in the organization, including 10 personality-based Entrepreneurial behaviors and 17 effective Entrepreneurial behaviors from the environment.